PEDAGOGICAL ERUDITION AS A FACTOR IN TRAINING HIGHLY QUALIFIED EDUCATORS: INTEGRATION OF ILLUSTRATIVE ACTIVITY TRAINING (Universal International Scientific Journal, 2026)
This article discusses the content and essence of pedagogical erudition, its role in the training of highly qualified educators, and its integration with visual activity classes in the educational process. The article analyzes practical ways to form pedagogical erudition, develop children's creative abilities through visual activity, and increase the professional competence of teachers.
Keywords: pedagogical erudition, educational pedagogue, visual activity, integration, quality of education, professional competence.